Sophie Go's lonely hearts club - Lim, Roselle (Berkley, 2022)
"A new heartfelt novel about the power of loneliness and the strength of love that overcomes it by critically acclaimed author Roselle Lim. Newly minted professional matchmaker Sophie Go has returned to Toronto, her hometown, after spending three years in Shanghai. Her job is made difficult when she is revealed as a fraud: she never actually graduated from matchmaking school. In a competitive market like Toronto, no one wants to take a chance on an inexperienced and unaccredited matchmaker, and soon Sophie becomes an outcast. In dire search of clients, Sophie stumbles upon a secret club within her condo complex: the Old Ducks, seven septuagenarian Chinese bachelors who never found love. Somehow, she convinces them to hire her, but her matchmaking skills are put to the test as she learns the depths of loneliness, heartbreak, and love by attempting to make the hardest matches of her life"--